A spanyol jogszokáskutatás első időszaka: Serrano, Unamuno Espejo gyűjtései - Matla, Gabriella (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2022)
The study provides an insight into the early period of Spanish legal custom research, highlighting the effect of Joaquín Costa’s legal custom program on collectors, whose careers were not determined by legal interest, but whose collections further enriched research and facilitated the incorporation of legal custom research into modern Spanish jurisprudence and history of law.